2021
DOI: 10.32598/bcn.2021.809.3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience-Informed Psychoeducation for Recovery: A Program to Promote Metacognition in People With Substance Use Disorders

Abstract: Background: A brief neuroscience-informed psychoeducation program (neuroscience-informed psychoeducation for recovery, NIPER) was developed to promote awareness (metacognition) in the main cognitive domains affected by drug and alcohol use to increase willingness to invest time and effort in the brain and cognition recovery process. The primary aim of this pilot study was to determine the feasibility and acceptability of the NIPER program and its potential effectiveness in terms of increasing metacognition, ps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the one hand, preliminary studies have suggested that psychoeducation might be useful to reduce alcohol consumption in subclinical samples (e.g., Gilder et al., 2017), to lower the impact of psychopathological comorbidities on alcohol use (e.g., post‐traumatic stress disorder; Bujarski, 2015) and to facilitate abstinence in the longer run (e.g., after more than 6 months postdetoxification; Kayaoğlu & Şahin Altun, 2022). Moreover, psychoeducation might be useful to improve major clinical variables (e.g., therapeutic alliance, insight, self‐evaluation, metacognition, e.g., Rezapour et al., 2021), to increase patients' awareness that their consumption is problematic, or to prepare patients to take an active part in the therapeutic program (e.g., neuroscience‐informed psychoeducation, Ekhtiari et al., 2017). On the other hand, however, it does not constitute by itself a powerful tool to promote long‐term abstinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, preliminary studies have suggested that psychoeducation might be useful to reduce alcohol consumption in subclinical samples (e.g., Gilder et al., 2017), to lower the impact of psychopathological comorbidities on alcohol use (e.g., post‐traumatic stress disorder; Bujarski, 2015) and to facilitate abstinence in the longer run (e.g., after more than 6 months postdetoxification; Kayaoğlu & Şahin Altun, 2022). Moreover, psychoeducation might be useful to improve major clinical variables (e.g., therapeutic alliance, insight, self‐evaluation, metacognition, e.g., Rezapour et al., 2021), to increase patients' awareness that their consumption is problematic, or to prepare patients to take an active part in the therapeutic program (e.g., neuroscience‐informed psychoeducation, Ekhtiari et al., 2017). On the other hand, however, it does not constitute by itself a powerful tool to promote long‐term abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…and to facilitate abstinence in the longer run (e.g., after more than 6 months postdetoxification;Kayaoğlu & Şahin Altun, 2022). Moreover, psychoeducation might be useful to improve major clinical variables (e.g., therapeutic alliance, insight, self-evaluation, metacognition, e.g.,Rezapour et al, 2021), to increase patients' awareness that their consumption is problematic, or to prepare patients to take an active part in the therapeutic program (e.g., neuroscience-informed psychoeducation,Ekhtiari et al, 2017). On the other hand, however, it does not constitute by itself a powerful tool to promote long-term abstinence.…”
mentioning
confidence: 99%
“…It further increases their motivation to experiment with the offered exercises (e.g. conjoint ERP and reducing FA) later on in the session and to do the homework task (Abramowitz et al, 2012; Baldisserotto et al, 2021; Grunes et al, 2001; Rezapour et al, 2021; Thompson‐Hollands et al, 2015). Since it was offered in an interactional setting (‘in exchange for the experiences of the patients and family members’), it offered the group members the opportunity to reflect on ‘their way’ of living with OCD, to learn from other's experiences and to find new ways of relating to other patients and family members.…”
Section: Therapeutic Work With the Families During Mftmentioning
confidence: 99%